2013
DOI: 10.3748/wjg.v19.i34.5665
|View full text |Cite
|
Sign up to set email alerts
|

5-ASA colonic mucosal concentrations resulting from different pharmaceutical formulations in ulcerative colitis

Abstract: IBD patients showed significant variability in mucosal 5-ASA concentrations depending on the type of formulation, and the highest mean concentration was achieved using pH-dependent-release formulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 28 publications
3
30
0
4
Order By: Relevance
“…Our finding that an increase in mucosal concentration is associated with quiescent disease is in line with studies that compare oral versus oral plus topical (combination) 5-ASA therapy. Placebo controlled trials showed that combination therapy is more effective than oral therapy alone [59], and pharmacokinetic studies established higher mucosal concentrations during combination therapy than during oral therapy alone [33,45,46,60,61]. Frieri et al [33] analysed both mucosal concentrations and therapeutic efficacy in UC patients using oral therapy versus combination therapy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our finding that an increase in mucosal concentration is associated with quiescent disease is in line with studies that compare oral versus oral plus topical (combination) 5-ASA therapy. Placebo controlled trials showed that combination therapy is more effective than oral therapy alone [59], and pharmacokinetic studies established higher mucosal concentrations during combination therapy than during oral therapy alone [33,45,46,60,61]. Frieri et al [33] analysed both mucosal concentrations and therapeutic efficacy in UC patients using oral therapy versus combination therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, several individual studies reported lower mucosal 5-ASA concentrations during inflammation. D'Inca et al [44] found a significant lower mucosal 5-ASA concentration during the active state of UC, both based on endoscopic and histological criteria, compared to quiescent UC (endoscopic active state 35.7 ± 5.7 ng/mg vs. remission 60.1 ± 8.0 ng/mg, p = 0.02, and histologic active state 35.5 ± 5.6 ng/mg vs. remission 67.5 ± 9.2 ng/mg, p < 0.001) [45]. Naganuma et al [46] detected an inverse correlation between the disease activity index of UC patients and mucosal van 5-ASA concentrations (r = 0.71, p < 0.001).…”
Section: Mucosal Concentration Disease and Activitymentioning
confidence: 96%
See 3 more Smart Citations